"But That's Not My Job": Employee Resistance to Extra-Role Tasks. Issue 4 (4th July 2021) - Duncan, Kaylin L.; Sias, Patricia M.; Shin, Yejin
ABSTRACT: Supervisors sometimes assign employees extra-role tasks, which are often perceived as unreasonable and can prompt employee resistance. In an experiment, we investigated employees' likelihood of declining an extra-role task (ERT) and the message characteristics associated with resistance. Results indicate that the more unreasonable employees perceived an ERT, the more likely they were to decline it. Employees were more likely to use polite strategies to resist an ERT when the assignment was communicated as a request and included explanation, appreciation, and acknowledgment. They were more likely to use impolite strategies when the ERT was assigned with messages that lacked those characteristics. These findings indicate how employees communicatively resist an ERT depends, in part, on how the ERT assignment is communicated by their supervisor.